1989
DOI: 10.1055/s-2008-1040523
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Alpha Interferon

Abstract: Alpha interferon is available worldwide as at least six dif-Alpha interferons have been used widely to treat chronic hepatitis C virus infection. These include recombinant inter-ferent products made by as many pharmaceutical companies. It is approved for human use in the European Union and the ferons, purified natural leukocyte, and lymphoblastoid inter-ferons. Alpha interferon is administered by subcutaneous or United States for several medical conditions, including hairy cell leukemia, chronic myelogenous le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
1
6

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(80 citation statements)
references
References 0 publications
2
71
1
6
Order By: Relevance
“…However, the same studies have indicated that a large proportion (> 50%) of the patients who respond to interferon subsequently relapse into chronic disease when it is withdrawn (Davis et al, 1990b;Lindsay et al, 1990). Furthermore, interferon-~ therapy is also associated with significant side-effects (Renault & Hoofnagle, 1989). Consequently there is a great need for development of novel chemo-or immunotherapeutic approaches to the treatment of HCV-induced disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, the same studies have indicated that a large proportion (> 50%) of the patients who respond to interferon subsequently relapse into chronic disease when it is withdrawn (Davis et al, 1990b;Lindsay et al, 1990). Furthermore, interferon-~ therapy is also associated with significant side-effects (Renault & Hoofnagle, 1989). Consequently there is a great need for development of novel chemo-or immunotherapeutic approaches to the treatment of HCV-induced disease.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic administration of interferon-a increases body temperature, induces anorexia at the beginning of the treatment, and often suppresses hematopoiesis in the bone marrow [2,3]. From the endocrinological aspect, it is well known that various cytokines, released from invaded inflammatory cells such as macrophages, affect the regulation of neuroendocrine function following peripheral immune reaction.…”
mentioning
confidence: 99%
“…General fatigue is one of the most prominent adverse effects ofIFN therapy and is usually recognized as early as within 2 weeks of treatment (14). The present patient complained of general fatigue which occurred as late as 3 months after the initiation of IFN therapy and might have been due to A-Vblock and/or sarcoidosis itself.…”
Section: Discussionmentioning
confidence: 69%